Understanding Urogenital Schistosomiasis-Related Bladder Cancer: An Update - Ishida, Kenji; Hsieh, Michael H. (Frontiers in Medicine, 2018)
Infection with Schistosoma haematobium leads to urogenital schistosomiasis, which has been correlated with the occurrence of bladder cancer. However, mechanisms responsible for this association have not yet been clearly identified. In this short review, we provide an update, highlighting the most recent studies on schistosome-associated bladder cancer, including those that focus on identifying changes in host biology during S. haematobium infection, as well as studies for the identification of potentially pro-carcinogenic parasite molecules, and we offer a discussion on some possible mechanisms driving schistosomal bladder cancer.